PARTISIPASI MASYARAKAT DALAM PENGELOLAAN USAHA EKOWISATA TAMAN NASIONAL TESSO NILO KABUPATEN PELALAWAN PROVINSI RIAU (Studi Kasus Di Desa Lubuk Kembang Bungo) - ", Susanto; Arief, Andi M Rifiyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research purposed to get know how the communities participation and how the management of ecotourism in tesso nilo national park lubuk kembang bunga village district ukui sub-district plalawan on the stage of development of ecotourism there and potential to be developed in the Tesso Nilo national park.This study used a qualitative method with descriptive approach to describe the actual state by collecting data and information in the field. The subject of the study researchers used a key informant as many as 16 people are concerned with sub-indicators. While data collection techniques in this study using observation, interviews, and documentation.Based on the research that has been done, the public response to community participation in the management of ecotourism businesses that occurred in the area of Tesso Nilo National Park is already underway in three participation that direct participation, indirect participation, and no participation, each of which has involved the participation of society in every, but the direct participation has not maximize the role of local communities or local in them.Key words : Community participation, ecotourism, Tesso Nilo National Park.